Formulasi dan Uji Stabilitas Fisik Sediaan Salep Dari Fraksi Daun Kemangi (Ocimun sanctum L) - Mustika Sari, Rahayu (Politeknik Tiara Bunda, 2023)
This basil plant (Ocimum Sanctum.Lin.) contains: essential oils, alkaloids, eugenol, rosmarinic acid, saponins, flavonoids, tannins and phenols. This study aims to determine the preparation of ointment from the basil leaf fraction that meets the requirements of the physical quality of the preparation and to determine the effect of variations in the ointment base from basil leaves by testing the physical stability of the preparation. This research was conducted using the one-way Anova statistical test followed by the Tukey test and the data were analyzed using Kurskal Wallis and Man Withney then tested for the physical properties and stability of the ointment which included organoleptic tests, homogeneity tests, pH tests, viscosity tests, dispersibility tests, and adhesion test. The results showed that basil leaf extract could be formulated into ointment preparations from the basil leaf fraction (Ocimum Sanctum L) into ointment preparations with various base variations that met the physical quality requirements of the preparation and in this study there was an effect of variations in the ointment base from the basil leaf fraction ( hydrocarbon base, absorption base and water soluble base) based on the physical stability test of the ointment preparation. So it can be concluded that the Basil leaf extracts and fractions can be formulated into ointment preparations (Ocimum Sanctum L) but do not meet the physical quality requirements of the preparation and have the effect of base variations on the ointment preparation